Cats and bats and things like that, and other wonderful things about God's world - Beers, V. Gilbert; Krisvoy, Juel. (Chicago, Moody Press, 1972)
Describes some of God's gifts in nature, such as the bats' sonar, the changing colors of leaves, and the life contained in a seed.
Keywords: Providence and government of God; Nature